Pemodelan dan Simulasi Rantai Pasok Mobil Honda - Audi Ramadhan; Safitra Aditya; Mohammad Afinil (Institut Transportasi dan Logistik Trisakti, 2020)
Cars are one of the needs of modern humans today. However, car price fluctuations are influenced by several factors, one of which is the supply chain factor. The supply chain in the delivery of a car has a share in these fluctuations. So the efficiency and effectiveness of the supply chain in shipping Honda cars need to be considered. This study aims to model the supply chain routes of Honda cars. This study uses the object delivery of Honda cars using the Agent Based method. The results of this study are the visualization and evaluation of Honda car supply chain route. The expectation of this research is become a consideration for companies to improve the efficiency and effectiveness of shipments.